Economic value of information - Baiget, Tomí s (Anuario ThinkEPI, 2010)
Review of concepts related to costs, prices and value of information, overview of the global information market, takeovers in 2009 and trends on strategies to sell information.
Keywords: Information market; Prices; Costs; Value; Mergers & Acquisitions; Pricing; Sales.